A Single Bout of Moderate Intensity Exercise Improves Concentration Level on Teenagers - Wijaya, Maharani Ayuputeri; Sulistiawaty, Nuniek Nugraheni; Wigati, Kristanti Wanito; Herawati, Lilik (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
ABSTRACTBackground: Physical exercise has a lot of benefit for health. However, the effect of cognitive function such as concentration in teenagers has yet been known.Aims: The objective of this study was to analyze the effect of a single bout or acute moderate intensity physical exercise on the level of concentration in teenagers.Methods: The subjects of this study were 32 16-18 years old teenagers, divided into two groups, control (C) and exercise (E) groups. Each group consisted of 8 boys and 8 girls. The E group did a single bout of moderate exercise using ergocycle. Physical exercise duration was 15 minutes, preceded by 5 minutes of warming up and then followed by 5 minutes of cooling down exercise. The concentration level was measured using the response period to sound stimulation (in second), measured with reaction time machine pre- and post-treatment. Faster response showed better concentration level and vice versa. Data were analyzed using paired T test, Wilcoxon Signed Ranks Test, independent T test, and Mann-Whitney test. The significance level was 5%.Result: There were significant differences of concentration level between pre- and post-exercise in E group (p= 0.004) and post-exercise concentration level between groups (p = 0.01). Exercise group had faster reaction time than C group (0.555±0.2 vs. 0.793±0.3, respectively).Conclusion: A single bout of moderate intensity exercise can improve the cognitive function showed by increased concentration level in teenagers.